Probing the structure of the V2 domain of human immunodeficiency virus type 1 surface glycoprotein gp120 with a panel of eight monoclonal antibodies: human immune response to the V1 and V2 domains. - Moore, J; Sattentau, Q; Yoshiyama, H; Thali, M; Charles, M; Sullivan, N; Poon, S; Fung, MS; Traincard, F; Pinkus, M (1993)
We have analyzed a panel of eight murine monoclonal antibodies (MAbs) that depend on the V2 domain for binding to human immunodeficiency virus type 1 (HIV-1) gp120. Each MAb is sensitive to amino acid changes within V2, and some are affected by substitutions elsewhere. With one exception, the MAbs were not reactive with peptides from the V2 region, or only poorly so. Hence their ability to bind recombinant strain IIIB gp120 depended on the preservation of native structure. Three MAbs cross-reacted with strain RF gp120, but only one cross-reacted with MN gp120, and none bound SF-2 gp120. Four MAbs neutralized HIV-1 IIIB with various potencies, and the one able to bind MN gp120 neutralized that virus. Peptide serology indicated that antibodies cross-reactive with the HxB2 V1 and V2 regions are rarely present in HIV-1-positive sera, but the relatively conserved segment between the V1 and V2 loops was recognized by antibodies in a significant fraction of sera. Antibodies able to block the binding of V2 MAbs to IIIB or MN gp120 rarely exist in sera from HIV-1-infected humans; more common in these sera are antibodies that enhance the binding of V2 MAbs to gp120. This enhancement effect of HIV-1-positive sera can be mimicked by several human MAbs to different discontinuous gp120 epitopes. Soluble CD4 enhanced binding of one V2 MAb to oligomeric gp120 but not to monomeric gp120, perhaps by inducing conformational changes in the oligomer.